The effect of indocyanine green-mediated photodynamic therapy as an adjunct to scaling and root planing in the treatment of chronic periodontitis: A comparative split-mouth randomized clinical trial - Saurabh H Shingnapurkar; Dipika K Mitra; Mitali Suresh Kadav; Rohit A Shah; Silvia V Rodrigues; Saurabh S Prithyani (Wolters Kluwer Medknow Publications, 2016)
Objective: The aim of this study was to assess the effect of adjunctive photodynamic therapy (PDT) (using 810 nm diode laser and Indocyanine green as photosensitizer) in chronic periodontitis. Materials and Methods: Patients with untreated chronic periodontitis were included. Treatment was done according to a split mouth design. All sites received periodontal treatment comprising scaling and root-planing (SRP). Test group were additionally treated with PDT. Plaque Index (PI), Gingival Index (GI), Probing Pocket Depth (PPD) and Relative Attachment Level (RAL) were evaluated at baseline, 1 month and 3 months. Results: Mean baseline values for PI, GI, PPD and RAL were not different in the test group and control group. Statistical significant difference in PPD and RAL, 3 months after treatment was seen in test group as compared to the control group. Conclusions: In patients with chronic periodontitis, clinical outcomes of conventional SRP can be improved by adjunctive PDT.